Improvement of quality of service through Wireless Early Regulation of Unresponsive Flows (WERUF) scheme - Sharina Binti Shuhaime (2023)
This thesis reports on future transmission technology that could replace or enhance the present transmission means (wireless/wired). The objectives of this project are to study the present and future telecommunications demands and to provide a possible solution on a certain weakness area that presently exists. The thesis discusses the background of communications technology, from the First Generation, Second Generation, Enhanced Second Generation, to the Third Generation Technology. It also discusses the weaknesses that exist in the present transmission technology. This thesis is also mainly focused on improving the condition by traffic shaping/profiling and improvements in Quality of Service in present communications technology.